Vračilo preveč izplačanih zneskov plač javnega uslužbenca - anomalija slovenskega plačnega sistema - Tancer Verboten, Mojca (Podjetje in delo, 2024)
The article examines the regulation of repayment of overpaid public servant’s salaries in Article 3a of the Public Sector Salary System Act. Based on the detailed substantial analysis of the history of this institute, drafting materials, opinions of the relevant ministries, theoretical discussions and, in particular, the extensive case law in this area, the authors point out the concerns and inconsistencies of the existing regulation and reflect on the need for a new approach to the regulation of this issue.
Keywords: javni uslužbenci; plačni sistem; prenova plačnega sistema; public sector salary system; public servants; repayment of overpaid salaries; salary system; salary system reform; vračilo preveč izplačanih zneskov plač; ZSPJS